Elizabeth Smart's Novel-Journal - Horne, Dee (Studies in Canadian Literature, 1991)
Elizabeth Smart's journals constitute the bulk of her writing; they are crucial to the development of her artistic form and play an integral role in her writing process. Smart's journals have distinctive characteristics -- truthfulness, credibility, compression, and intimacy -- and Smart uses them to create a new literary form: the novel-journal. Her journals evolve from external to internal observations, moving towards a developed form in which Smart portrays her life as crafted art. Smart makes minimal changes between the seven corresponding sections of her journal drafts and the published text of By Grand Central Station I Sat Down and Wept: the changes result in a more emotive, unified, clear, and focused text. Shirley Neuman's statement that "the writing is the life" is an apt description of Smart's life and writing -- just as Smart lives segments of her life as art, so she also sees writing as life.